Job burnout of English teachers in private higher education institutions in Shandong, China - Chen, Peipei (Panpacific University : [s.n.], 2020)
Teaching is demanding job and teachers are at a high risk of job burnout. For some reasons, teachers in private higher education institutions suffer most from job burnout and so are the singlish teachers in private higher education institutions, which negatively affect the quality of higher education. The study intended to investigate the job burnout of English teachers of private higher education institutions in Shandong, China. A survey questionnaire was conducted as the research instrument to identify the profiles and the level of job burnout of English teachers in five private higher education institutions in Shandong and the collected data were described and analyzed. Results indicated that English teachers in private higher institutions in Shandong, China experienced a high level of job burnout and there were no significant differences among the levels of English teachers by different genders, ages, marital status and years of teaching, and there is a significant difference between the levels of emotional exhaustion of English teachers when grouped by age. With this, an action plan was proposed and shall be implemented.
References: pages 85-103.
CHED-La Union
Keywords: Private schools -- China